Territorial cohesion; from the European to the regional agenda: conceptual transposition or conceptual redefinition? - Santinha, Gonçalo (2018)
Since the 1990s, the debate around Europeanization has been continuous in planning and political discourses. But if economic and social cohesion were already deeply rooted in European policies, only after the Green Paper on Territorial Cohesion (2008) and the signing of the Treaty of Lisbon (2009), was a third dimension added: Territorial Cohesion. However, this is still not a consensual term. The ambiguity in defining and achieving it represents a challenge to various national and regional actors, intent in articulating with EU guidelines. This paper thus wishes to understand how, and in what terms, Territorial Cohesion is being transposed from the EU policy agenda to domestic policies. Using Portugal as a test-bed, the paper compares European with national documents discussing 'Territorial Cohesion', by means of a Qualitative Content Analysis. From this analysis contributions to the debate on Europeanization are made, thus assisting public policy making and territorial planning in Portugal and other European countries.